Effect of Orthodontic Appliances on the Oral Environment and Microbiome - Mulimani, Priti; Popowics, Tracy (Frontiers in Dental Medicine, 2022)
Orthodontic treatment is an appliance-intensive endeavor, where an array of mechanical devices is used to bring about tooth movement. By virtue of remaining in close proximity to the enamel, gingiva and periodontal ligament intra-orally over a prolonged period of time, orthodontic appliances have a significant impact on the paradental tissues, oral environment and oral microbiome. Orthodontic appliances, by acting as anchors for biofilm and plaque formation, accumulate bacteria and other microorganisms in amounts unfavorable for maintenance of healthy equilibrium. The resulting loss of balance in the oral microbiome causes dysbiosis, which manifests clinically as increased enamel demineralization, dental caries and periodontal disease. Mechanical removal of the accumulated plaque by maintaining rigorous oral hygiene has been proven to be the single most important factor to mitigate the harmful effects of dysbiosis. This review investigates how each of the various components of orthodontic appliances, different types of appliances and unique surface properties of biomaterials have contributory effects at the interface of orthodontic biomaterials and oral biology. The information thus obtained will be critical in instituting the best diagnostic and therapeutic measures at the clinical level. It will also be instrumental in devising improvements and providing new directions for future research in general and precision orthodontics in particular.